2008
DOI: 10.1016/j.accfor.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Public sector reforms, privatisation and regimes of control in a Chinese enterprise

Abstract: The Chinese economic reform has recently become a major focus of attention around the world. The underlying rationale for the Chinese government's privatisation and public sector reforms is the view that reformed state enterprises and privately managed firms will demonstrate superior management control and better performance, and hence encourage economic growth and employment. There are very few intensive case studies published in English journals studying whether firms privatised in China have reversed previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Political constraints continue to influence production and investment decisions (Skousen & Yang, 1998) and even, in some cases, interfere in the recruitment, promotion and dismissal of employees in Chinese SOEs, despite being exposed to market forces (O'Connor et al, 2006). Similar conclusions were drawn in another study (Xu & Uddin, 2008) that found that market-based reforms in Chinese SOEs resulted in powerful and wealthy state managers rather than the desired Western-centric, delegated management controls.…”
Section: Culture and Politicssupporting
confidence: 67%
“…Political constraints continue to influence production and investment decisions (Skousen & Yang, 1998) and even, in some cases, interfere in the recruitment, promotion and dismissal of employees in Chinese SOEs, despite being exposed to market forces (O'Connor et al, 2006). Similar conclusions were drawn in another study (Xu & Uddin, 2008) that found that market-based reforms in Chinese SOEs resulted in powerful and wealthy state managers rather than the desired Western-centric, delegated management controls.…”
Section: Culture and Politicssupporting
confidence: 67%
“…Here, management accounting has made the local both governable and controllable (Ilcan and Phillips 2010) through the NPM agenda, which promotes political interests (Modell 2001(Modell , 2012aWatkins and Arrington 2007;Chang 2009). Although recent NPM research in the context of LDCs has reported that political and cultural factors result in unintended, idiosyncratic consequences in management accounting practices (Uddin and Tsamenyi 2005;Rahman et al 2007;Xu and Uddin 2008;Hopper et al 2009), we have yet to ascertain how such projects have affected management, governance and political domains; how management accounting can act as an instrument of mediation; and how accounting can be made societally relevant.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, those responsible for setting the Chinese accounting standards did allow the pooling of interests method of accounting for business combinations, despite the prohibition of this method by both the FASB and the IASB. The decision by Chinese standards setters to authorize the pooling of interests method reflects the large scale industrial reorganization taking place in China (Xu & Uddin ). Baker et al .…”
Section: Business Combination Accounting Regulationsmentioning
confidence: 99%
“…By contrast, those responsible for setting the Chinese accounting standards did allow the pooling of interests method of accounting for business combinations, despite the prohibition of this method by both the FASB and the IASB. The decision by Chinese standards setters to authorize the pooling of interests method reflects the large scale industrial reorganization taking place in China (Xu & Uddin 2008). Baker et al (2010) argue that the pooling method provides greater flexibility to banks and large industrial groups when recognizing their operations, without the need to refer to unreliable fair market value measures, as required by IFRS 3 Business Combinations.…”
Section: Business Combination Accounting Regulationsmentioning
confidence: 99%